Achieving goals and making meanings: Toward a unified model of recreational experience. (September 2018) - Fix, Peter J.; Brooks, Jeffrey J.; Harrington, Andrew M.
Abstract: Understanding recreational experiences is a longstanding research tradition and key to effective management. Given the complexities of human experience, many approaches have been applied to study recreational experience. Two such approaches are the experiential approach (based in a positivistic paradigm) and emergent experience (based in an interpretive paradigm). While viewed as being complementary, researchers have not offered guidance for incorporating the approaches into a common model of recreational experience. This study utilized longitudinal, qualitative data to examine aspects of recreational experience posited by these two approaches. Results provided a framework for synthesizing across the two approaches. Respondents had clear pre-activity expectations, and most respondents realized their expected outcomes. This supports the experiential approach. Of the 48 activity narratives, 27 experienced something unexpected, and 45 described process-oriented, intrinsic motivation, suggesting evidence of emergent and unique characteristics specific to an individual's realization of recreational experience. This supports the application of the emergent experience approach to understand how individuals create meaning from recreational engagements. The paper proposes a model for integrating results of the two approaches. While not advocating for any specific approach, the findings can serve as an example of building a holistic model of the outdoor recreation experience. The purpose of the model is to allow for a more complete understanding of how individuals create recreation experiences, more complete documentation of the benefits of outdoor recreation for both researchers and managers, and better synthesis across studies. Management implications: Information regarding the recreational experience can assist in implementing informed management decisions. This paper presents commonly applied approaches and discusses their differences and the benefits when combining them. The paper gives insights into different approaches focusing on desired experiences, emergent experiences, satisfaction, or long-term benefits and the related management questions. These help managers to select the most suitable approach for their respective challenges.